2020
DOI: 10.1080/14681811.2020.1821180
|View full text |Cite
|
Sign up to set email alerts
|

Classroom implementation of national sexuality education curricula in four low- and middle-income countries

Abstract: School-based comprehensive sexuality education (CSE) can help adolescents acquire crucial knowledge and skills to achieve their full potential, particularly in low-and middle-income countries with higher rates of negative sexual and reproductive outcomes. While many low-and middle-income countries have developed CSE curricula, little is known about how these are implemented in the classroom. This multi-country mixed-methods study analysed challenges to the implementation of national CSE curricula in schools in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 14 publications
2
11
0
11
Order By: Relevance
“…There is a need for increased awareness and priority building measures to garner community and leadership commitment to work towards developing and integrating sexuality education in the curriculum. Rigorous teacher training to deliver content on sexuality education has also been emphasized as an integral part of successfully integrating CSE into the curriculum [ 49 , 50 , 51 ]. In a study conducted in sub-Saharan Africa, one of the major barriers identified was the reluctance of teachers to teach sexuality education content [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a need for increased awareness and priority building measures to garner community and leadership commitment to work towards developing and integrating sexuality education in the curriculum. Rigorous teacher training to deliver content on sexuality education has also been emphasized as an integral part of successfully integrating CSE into the curriculum [ 49 , 50 , 51 ]. In a study conducted in sub-Saharan Africa, one of the major barriers identified was the reluctance of teachers to teach sexuality education content [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous teacher training to deliver content on sexuality education has also been emphasized as an integral part of successfully integrating CSE into the curriculum [ 49 , 50 , 51 ]. In a study conducted in sub-Saharan Africa, one of the major barriers identified was the reluctance of teachers to teach sexuality education content [ 49 , 50 , 51 ]. The authors argued that the discomfort of teachers may nurture the perception of students that sexuality-related topics are taboo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to older women, young women were more heavily influenced by their friends’ opinions. For young people who are unable to access health facilities and who may lack comprehensive sexuality education in school [ 50 ], friends may provide a key source of information on contraceptives. The strong influence of friends on young women’s opinions about contraception could potentially be leveraged through tools such as social media, where experts and influencers can disseminate accurate contraceptive information that is then picked up and shared by young people among their social networks.…”
Section: Discussionmentioning
confidence: 99%
“…The content of CSE remains contested in many parts of the world due to variations in framing and notions of sexuality and fears related to disrupting identities and values of the communities and compromising children's innocence [12]. In addition, people fail to agree on what "comprehensive" entails in the context of CSE [13]. Because of these varied understandings and fears about CSE, several sexuality education guidelines have been developed [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%